2012
DOI: 10.1371/journal.pone.0039645
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Plasmodium vivax Reveals Both Short and Long Latency Relapse Patterns in Kolkata

Abstract: Background The Plasmodium vivax that was once prevalent in temperate climatic zones typically had an interval between primary infection and first relapse of 7–10 months, whereas in tropical areas P.vivax infections relapse frequently at intervals of 3–6 weeks. Defining the epidemiology of these two phenotypes from temporal patterns of illness in endemic areas is difficult or impossible, particularly if they overlap. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 17 publications
6
42
1
Order By: Relevance
“…Thus, in Kolkata, CQ alone was 99% and CQ plus PQ was 100% effective against P. vivax malaria. Similar observations were also made from 1998 to 2001 (29) (30). Therefore, during the past 15 years, the efficacy of CQ remained unchanged in P. vivax malaria, but in P. falciparum malaria, the CQ resistance level reached 76.3% (31).…”
Section: Discussionsupporting
confidence: 78%
“…Thus, in Kolkata, CQ alone was 99% and CQ plus PQ was 100% effective against P. vivax malaria. Similar observations were also made from 1998 to 2001 (29) (30). Therefore, during the past 15 years, the efficacy of CQ remained unchanged in P. vivax malaria, but in P. falciparum malaria, the CQ resistance level reached 76.3% (31).…”
Section: Discussionsupporting
confidence: 78%
“…This suggested that the prescribed primaquine regimen as per the WHO recommendations [24] possibly was not absolutely efficient for preventing all relapses. This kind of therapeutic response variability and inadequacy has also been observed in many endemic regions [20,25,26]. However, it must be pointed out that, since the primaquine treatment provided to study subjects was an unmonitored 14-day course, an absolute compliance cannot be assured.…”
Section: Discussionmentioning
confidence: 93%
“…As a result of their extremely high within population diversity, antigen markers paired with extremely polymorphic microsatellites have identified and tracked individual clones over time within individuals with a high degree of certainty. [23][24][25] As mentioned above, the high diversity and maintenance of balanced allele frequencies by immune selection makes antigen markers extremely useful for measuring MOI and FOI because they ensure the lowest probability of clones having the same allele, and thus being indistinguishable. On the other hand, the pattern of diversity in antigens limits the detection of divergence between populations; therefore, antigen markers should be used with caution if the aim is to measure underlying patterns of gene flow between populations.…”
Section: Antigen Locimentioning
confidence: 99%